Lateral recumbent position versus kneeling prone position combined with unprotected perineal delivery in natural childbirth: implication for clinical care - Xiuli Dai; Nan Jin (BMC Pregnancy and Childbirth)
Abstract Background Posture management significantly influences the natural childbirth process and the maternal experience. The aim of this study is to analyze the effects of the lateral recumbent position versus the kneeling prone position combined with unprotected perineal delivery in natural childbirth, providing evidence-based support for clinical maternal care and posture management. Methods This research constitutes a retrospective cohort investigation, encompassing a period from January 2022 to December 2023, and focusing on women in labor who experienced childbirth at our medical facility. The study meticulously assessed and compared the characteristics and clinical outcomes of those who adopted the lateral recumbent position with those who utilized the kneeling prone position during the process of natural childbirth. Results A total of 168 women in labor were included, 86 women in labor underwent lateral recumbent position and 82 women in labor underwent kneeling prone position for natural childbirth. There were no statistical differences in first, second, third and total stage of labor between lateral recumbent position group and kneeling prone position group were found (all P > 0.05). Visual Analogue Scale (VAS) and Self-Rating Anxiety Scale (SAS) score after labor in lateral recumbent position group were statistically lower than that of kneeling prone position group(all P < 0.05). The lateral recumbent position reduced the likelihood of episiotomy and perineal edema, the severity of perineal lacerations compared with kneeling prone position for natural childbirth (all P < 0.05). Conclusion Lateral recumbent position in natural childbirth offers the advantage of reducing perineal trauma, alleviating maternal pain and anxiety, and may be therefore deemed worthy of utilization in clinical maternal care.